Model kompetensi sosial mahasiswa calon guru: Studi dengan penerapan Structural Equation Modelling: Social competence model of prospective teacher students: A study using Structural Equation Modeling - Suharni, Suharni; Akbar, Sa'dun; Hitipeuw, Imanuel; Eva, Nur (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Social competence is a life skill that prospective teacher students must possess. Unfortunately, many prospective teacher students have low social competence. This study aims to test the social competence model of prospective teacher students in terms of authoritative parenting patterns and internal locus of control mediated by emotional regulation. The research participants were students of the Faculty of Teacher Training and Education recruited using purposive sampling techniques (n = 350). The research instruments consisted of the Social Competence in High Education Questionnaire (α=0.906), Parenting Style Dimension Questionnaire (α=0.884), Internal Locus of Control scale (α=0.933), and Emotion Regulation Questionnaire (α=0.874). All research instruments have been validated using Confirmatory Factor Analysis (CFA). The research data were analyzed using Structural Equation Modeling (SEM). The study results showed that empirical data supported the proposed research model. The implications of this study require Universities to provide students with certain strategies to develop social competence, especially in the Faculty of Education.